2010
DOI: 10.1002/ajpa.21331
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary 3D computed tomography study of the human maxillary sinus and nasal cavity

Abstract: Despite centuries of investigation, the function of the maxillary sinus (MS) and underlying patterns governing its form remain elusive. In this study, we articulate a methodology for collecting volumetric data for the MS and nasal cavity (NC) from computed tomography (CT) scans and report details for a small sample of 39 dried human crania of known ecogeographic provenience useful for assessing variation in MS size and shape. We use scaling analyses to preliminarily test the hypothesis that volumes of the nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 75 publications
10
75
2
1
Order By: Relevance
“…The extent of the maxillary sinus, which is the most studied of the paranasal sinuses, is known to be influenced in New World monkeys by the relative dental size and the growth of adjacent skeletal structures of the maxilla; histomorphometric studies have confirmed that the growing maxillary sinus extends into areas without constraints (Smith et al, ). In humans, the maxillary sinus is larger in individuals with larger faces and it accommodates in the available space left by the lateral nasal walls: individuals with narrower nasal cavities present larger maxillary sinuses (Butaric & Maddux, ; Butaric et al, ; Holton et al, ). However, a recent study of Maddux and Butaric (), which compares samples of different geographic origins, shows that the maxillary sinus extends more laterally and more inferiorly in individuals with taller zygomaticomaxillary interfaces (e.g., taller midfacial skeletons) compared to individuals with shorter midfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of the maxillary sinus, which is the most studied of the paranasal sinuses, is known to be influenced in New World monkeys by the relative dental size and the growth of adjacent skeletal structures of the maxilla; histomorphometric studies have confirmed that the growing maxillary sinus extends into areas without constraints (Smith et al, ). In humans, the maxillary sinus is larger in individuals with larger faces and it accommodates in the available space left by the lateral nasal walls: individuals with narrower nasal cavities present larger maxillary sinuses (Butaric & Maddux, ; Butaric et al, ; Holton et al, ). However, a recent study of Maddux and Butaric (), which compares samples of different geographic origins, shows that the maxillary sinus extends more laterally and more inferiorly in individuals with taller zygomaticomaxillary interfaces (e.g., taller midfacial skeletons) compared to individuals with shorter midfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Association between traits can be inferred by comparing the ontogeny (i.e., growth trajectories) of different modules or anatomical parts or by direct test of correlation between traits (Lieberman, ). Based on previous studies on different paranasal sinuses, it is expected that the FS is structurally and developmentally associated with other variables, such as: (a) cranial size (Curtis et al, ; Zollikofer et al, ); (b) dimensions of adjacent structures, for example, nasal size (Butaric & Maddux, ; Butaric, McCarthy, & Broadfield, ; Holton, Yokley, & Butaric, ; Maddux & Butaric, 2017); and c) bone thickness and thickness of the glabellar region, as the bony environment provides the space to enable/constrain FS expansion (Curtis et al, ; Farke, ; Vinyard & Smith, ). The ontogenetic analysis of the FS in relation to these structures provides insight into the underlying mechanisms (e.g., the opportunistic pneumatization hypothesis) that shape the observed morphological variation among populations and species (Prossinger, ).…”
Section: Introductionmentioning
confidence: 99%
“…A relationship has been found between climatic factors and morphology of the face in general (Roseman, 2004;Harvati and Weaver, 2006a;Hubbe et al, 2009), the midface (Evteev et al, 2014), nasal aperture and cavity (e.g., Wolpoff, 1968;Noback et al, 2011), sinus volume (Shea, 1977; but see Rae et al, 2003;Butaric et al, 2010) and cranial size (Beals et al, 1984;Harvati and Weaver, 2006a), suggesting adaptive selection. This selection signal is strongly influenced by populations from extremely cold regions (Roseman, 2004;Weaver, 2006a, 2006b;Hubbe et al, 2009).…”
Section: Population History and Climatementioning
confidence: 96%
“…More recently, there was a notable study of correlations between the different volumes of cranial regions and face size [18], as well as studies on differences in volumes among different regions of the brain based on sex [19]. As for the bone volume studies on the postcranial skeleton, the purpose with which they have been performed is variable, with an emphasis on the interest in clinical practice to observe anomalies during growth [20] or to observe volume differences in the articulation cartilage based on sex [21,22].…”
Section: Discriminant Powermentioning
confidence: 99%